Delay-dependent exponential H ∞ filtering for discrete-time switched delay systems - Wang, Dong (2013)
In this paper, the problem of delay-dependent exponential H ∞  filtering for discrete-time switched delay systems is investigated under average dwell time switching signals. Time delay under consideration is interval time-varying in the states. By introducing a proper factor to construct a novel Lyapunov-Krasovskii function and using average dwell time approach, sufficient conditions for the solvability of this problem, dependent on the upper and lower bounds of time-varying delay, are obtained in terms of linear matrix inequalities. A numerical example is presented to demonstrate the effectiveness of the developed results.